Sistema informático para la Cooperativa de Ahorro y Crédito Tawantinsuyu Ltda. - Chasi Chiluisa, Milton Israel (2019)
The technological proposal sought to create and implement a system that provides solutions to the problems that exist in the institution of the Savings and Credit Cooperative Tawantinsuyu Ltda., Because it did not have a computer system that stored relevant information of the different processes they perform the employees of the institution, for which, satisfactory results were not obtained. For the development of the software we worked with the Scrum Methodology, because it offers the fulfillment of the expectations and the flexibility to changes, which makes it effective to work. The implemented system is responsible for generating modules, sub modules with their respective user roles in order to store files for each of the partners, in addition to generating processes that are performed in the box area according to the assigned role for each worker, in order to improve the quality of service and attention to the partner, reducing time and resources. In addition, make the institution known in other places through the internet. The system is easy to use for the worker, which will facilitate processes for better attention of each of the partners. A bibliographic research was carried out, gathering information related to current research, process management, which provided a deep knowledge about the object of study, for the development of the application the SCRUM methodology was used, the development tools as PHP programming language , MySQL database, Framework Laravel and a Hosting acquired by the cooperative. With the respective tests of each Sprint an optimal result of the system was obtained that meets all the requirements requested by the financial institution.